Circulating CD4+CD28null T Cells May Increase the Risk of an Atherosclerotic Vascular Event Shortly after Kidney Transplantation - Michiel G. H. Betjes; Willem Weimar; Nicolle H. R. Litjens (Journal of Transplantation)
Proinflammatory CD4+ T cells without the costimulatory molecule CD28 (CD4+CD28null T cells) are expanded in patients with end-stage renal disease (ESRD) and associated with atherosclerotic vascular events (AVE). In a prospective study, the number of circulating CD4+CD28null T cells was established in 295 ESRD patients prior to receiving a kidney allograft. Within the first year after transplantation, an AVE occurred in 20 patients. Univariate analysis showed that besides a history of cardiovascular disease (CVDpos, HR 8.1, ), age (HR 1.04, ), dyslipidaemia (HR 8.8, ), and the % of CD4+CD28null T cells (HR 1.04 per % increase, 95% CI 1.00–1.09, ) were significantly associated with the occurrence of a posttransplantation AVE. In a multivariate analysis, only CVDpos remained a significant risk factor with a significant and positive interaction between the terms CVDpos and the % of CD4+CD28null T cells (HR 1.05, 95% CI 1.03–1.11, ). Within the CVDpos group, the incidence of an AVE was 13% in the lowest tertile compared to 25% in the highest tertile of % of CD4+CD28null T cells. In conclusion, the presence of circulating CD4+CD28null T cells is associated with an increased risk for a cardiovascular event shortly after kidney transplantation.